Barriers to early detection and management of oral cancer in the Asia Pacific region. Issue 2 (April 2022) - Ng, Sin Wi; Syamim Syed Mohd Sobri, Sharifah Nur; Zain, Rosnah binti; Kallarakkal, Thomas George; Amtha, Rahmi; Wiranata Wong, Felix A; Rimal, Jyotsna; Durward, Callum; Chea, Chanbora; Jayasinghe, Ruwan Duminda; Vatanasapt, Patravoot; Saleha binti Ibrahim Tamin, Nor; et al.
Objective: Oral cancer is amenable to early detection but remains a prominent cause of mortality in the Asia Pacific region. This study aimed to identify barriers to early detection and management of oral cancer in the Asia Pacific region. Methods: A mixed-methods approach was employed triangulating findings from a survey and focus groups. The survey was conducted among seven representative members of the Asia Pacific Oral Cancer Network (APOCNET) across six countries. Focus groups were conducted to gain deeper insights into the findings of the survey. Results: The identified barriers were a lack of national cancer control strategies and cancer registries and the limited availability of trained health care professionals. Overcoming these challenges in the Asia Pacific region where resources are scarce will require collaborative partnerships in data collection and novel approaches for continuous professional training including eLearning. Further, to overcome the lack of trained health care professionals, innovative approaches to the management of oral potentially malignant lesions and oral cancer including telemedicine were suggested. Conclusion: The findings of this study should be taken into account when charting national cancer control plans for oral cancer and will form the basis for future collaborative studies in evaluating effective measures to improve oral cancer detection and management in low- and middle-income countries.